Academic Integrity: Putting Policy into Practice - Schofield, Susie (Canadian Perspectives on Academic Integrity, 2021)
On first reading of the University of Dundee’s Policy on Academic Misconduct seems eminently sensible, fair and clear. The Policy classifies plagiarism cases as 1 (very minor), 2 (minor) and 3 (serious), giving examples of each to inform the academic community. There is guidance on how all three should be handled, ranging from additional educational support through written warning through a hearing from a formal academic misconduct panel. As Associate Dean Quality Assurance and Standards at our Medical School I oversee how this policy is both enacted and data collected across the school. This paper outlines how we have operationalised the policy for a distance learning course with a thousand students and over 50 markers, based both within the Centre and globally. The programme is a masters in medical education, with about a third of the students based overseas, about 90% medical doctors, the others being allied health professionals, dentists, nurses and vets. The studies are all online at a distance, and assignments are in the main written. They are submitted, marked ad moderated via Turnitin, and students are encouraged to engage with the similarity report before finalising their submissions. I summarise the policy and identify various issues and how the Centre has sought to solve these. I present the process we have developed so far, our rationale behind each decision made and how going forward we are evaluating this process. I discuss our assessment strategy, including our underpinning pedagogical philosophy and how these have informed the decisions we have taken. I give an overview of both our student and our marker induction and faculty development for our core staff, who as module leads moderate the process. I present some initial statistics on student uptake of the various elements. I describe the development of an efficient and effective reporting process, codeveloped between academics and professional services, and the next stages of this development as we move to the piloting stage. I finish with some current questions we have on how we can support the students further as they navigate through the academic discourse around misconduct, learning and enacting the language, not least the challenges of collaboration versus corroboration and self-plagiarism in a course ending with a capstone assessment.